THE ROLE OF LANGUAGE AND CULTURE IN THE CONTEXT OF CORONAVIRUS - Harutyunyan, Narine (Armenian Folia Anglistika, 2022)
The article is devoted to the analysis of new words and phrases that come to dominate global discourse and have made their way into language as a result of the pandemic. The aim of the study is to determine the impact of the COVID-19 pandemic on the formation of a special layer of the «coronavirus» language of the current moment, the appearance of neologisms included in the event context. The novelty of the research lies in the fact that the analysis of the pandemic realities is carried out by taking into account the famous typology of cultural dimensions developed by Geert Hofstede. The article also deals with extralinguistic conditions for creating new lexical units and examines the impact of the COVID-19 outbreak on linguistic reality. It also highlights the cultural characteristics of the perception of certain peoples of the new reality, notes the differences in response to changes and prohibitions during the ongoing pandemic. The main research methods are the descriptive method, the comparative method, the analysis of lexical definitions. The sources were articles on Internet sites, WhatsApp, the social network Instagram, Tweeter. Each period of serious breakdown leads to a change in the vocabulary and socio-cultural realities.
Keywords: coronavocabulary; neologisms; coronaspeak; pandemic; cultural dimensions